FMNL1 mediates nasopharyngeal carcinoma cell aggressiveness by epigenetically upregulating MTA1. Issue 48 (29th November 2018) - Chen, Wen-Hui; Cai, Mu-Yan; Zhang, Jia-Xing; Wang, Feng-Wei; Tang, Lin-Quan; Liao, Yi-Ji; Jin, Xiao-Han; Wang, Chen-Yuan; Guo, Ling; Jiang, Yi-Guo; Ren, Cai-Ping; Mai, Hai-Qiang; et al.
Abstract It has been suggested that formin-like protein 1 (FMNL1) plays an important role in the pathogenic process of several hematopoietic malignancies. In this study, we performed a series of in vivo and in vitro assays to elucidate the biological functions ofFMNL1 and underlying mechanisms in human nasopharyngeal carcinoma (NPC) pathogenesis. Herein, we report that high expression of FMNL1 in NPC is positively associated with an aggressive disease and/or poor patient survival. Ectopic overexpression of FMNL1 in NPC cells substantially promoted cell invadopodia formation, epithelial-mesenchymal transition (EMT) and invasiveness, whereas depletion of FMNL1 potently suppressed NPC cells invadopodia formation, EMT, and invasive/metastatic capacities. We further show that FMNL1 could enhance NPC cell aggressiveness by increasing a key downstream target, the metastasis-associated protein 1(MTA1 ) gene. Importantly, ectopic overexpression of FMNL1 in NPC cells markedly improved the binding of HDAC1 with Profilin2 in the cytoplasm and suppressed the enrichment of HDAC1 on the promoter ofMTA1 and thereby, leading to an increasedMTA1 transcription and expression. Furthermore, in addition to the amplification ofFMNL1 gene, decreased level of miR-16 in NPCs is another critical mechanism to upregulate FMNL1 expression. These results, collectively, provide first-line of evidences that high expression of FMNL1, resulted from decreased miR-16 and/orMTA1 amplification, has a potent oncogenic role to drive the development and aggressive process of NPC by upregulating MTA1, and FMNL1 might be employed as a new prognostic biomarker and therapeutic target for human NPC.